2019
DOI: 10.1111/jdi.13116
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of albuminuria and renal dysfunction, and related clinical factors in Japanese patients with diabetes: The Japan Diabetes Complication and its Prevention prospective study 5

Abstract: Aims/Introduction To clarify the prevalence of albuminuria and renal dysfunction, and related factors in Japanese patients with diabetes, we analyzed the baseline data of the Japan Diabetes Complication and its Prevention prospective study. Materials and Methods We used the data of 355 patients with type 1 diabetes and 5,194 patients with type 2 diabetes to evaluate the prevalence of albuminuria and renal dysfunction, and related factors. A binomial logistic regression analysis was used to investigate independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
(40 reference statements)
0
16
0
3
Order By: Relevance
“…Another cross-sectional survey in Chinese rural residents (including 23,869 participants) demonstrated that the overall prevalence of chronic kidney disease in participants with diabetes was 35.5% [63]. Additionally, the high prevalence of abnormal kidney function among diabetic patients has been consistently reported in populations living in the United States [62], United Arab Emirates [64], Japan [65], Palestine [66], China [63, 67], Taiwan [68], and Europe [6971]. Moreover, T2D probably predicts progression of chronic kidney disease, and the presence of diabetic kidney disease seems to be associated with poor cardiovascular risk profile, especially in elderly individuals [71, 72].…”
Section: Unanswered Issues and Practical Considerations Regarding mentioning
confidence: 99%
“…Another cross-sectional survey in Chinese rural residents (including 23,869 participants) demonstrated that the overall prevalence of chronic kidney disease in participants with diabetes was 35.5% [63]. Additionally, the high prevalence of abnormal kidney function among diabetic patients has been consistently reported in populations living in the United States [62], United Arab Emirates [64], Japan [65], Palestine [66], China [63, 67], Taiwan [68], and Europe [6971]. Moreover, T2D probably predicts progression of chronic kidney disease, and the presence of diabetic kidney disease seems to be associated with poor cardiovascular risk profile, especially in elderly individuals [71, 72].…”
Section: Unanswered Issues and Practical Considerations Regarding mentioning
confidence: 99%
“…Finally, those with type 1 and 2 diabetes were not differentiated in our study. However, most of the people aged 40 and older who were diagnosed with diabetes were likely to have type 2 diabetes because of its higher prevalence in the general population (approximately 95%) [23,24]; hence, it can be assumed that most of the participants who initiated treatment in this study had type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that the incidence of low eGFR with normoalbuminuria has been increasing in type 2 diabetes [10,12,13]. Pathological findings revealed that tubulointerstitial and vascular lesions tended to be more advanced in participants with type 2 diabetes and CKD with normoalbuminuria than those in participants with microalbuminuria or macroalbuminuria [11,14,15].…”
Section: Discussionmentioning
confidence: 99%